Radio frequency hyperthermia system for skin tightening effect by filled waveguide aperture antenna with compact metamaterials - Kim, Ikhwan; Lee, Dong-Min; Shin, Jae-Woo; Lee, Gyoun-Jung; Kim, Eun-Seong; Kim, Nam-Young (Frontiers in Bioengineering and Biotechnology, 2024)
Radio frequency (RF) hyperthermia focuses on raising the target area temperature to a value exceeding 45°C. Collagen is stimulated when the temperature rises to 45°C at the dermal layer, resulting in skin tightening. However, most studies on RF hyperthermia have focused on tumor ablation or using electrodes to radiate an electromagnetic field, which is highly inefficient. This study proposed a non-invasive RF hyperthermia skin-tightening system with a compact metamaterial-filled waveguide aperture antenna. The proposed RF system increased the temperature by 11.6°C and 35.3°C with 20 and 80 W of 2.45 GHz RF power, respectively, within 60 s and exhibited a very focused effective area. Furthermore, a metamaterial was proposed to reduce the size of the waveguide aperture antenna and focus the electromagnetic field in the near-field region. The proposed metamaterial-filled waveguide aperture antenna was compact, measuring 10 mm × 17.4 mm, with a peak gain of 2.2 dB at 2.45 GHz. The measured hyperthermia performance indicated that the proposed RF system exhibited better power- and time-efficient hyperthermia performance than other RF hyperthermia systems in the cosmetic skin lifting commercial market. The proposed RF hyperthermia systems will be applied into a new generation of beauty cosmetic devices.